ФОРМУВАННЯ ГОТОВНОСТІ МАЙБУТНІХ ВЧИТЕЛІВ ДО ПРОФІЛЬНОГО НАВЧАННЯ СТАРШОКЛАСНИКІВ (Педагогіка вищої та середньої школи, 2022)
The article deals with the conception of readiness for different kinds of activities and professional oriented training. The conditions which will have a positive influence on forming of prospective teacher readiness for professional oriented training of senior pupils are submitted for consideration.